Molecular prevalence and risk factors associated with tick-borne pathogens in cattle in western Kenya - Chiuya, T.; Villinger, J.; Masiga, D.K.; Ondifu, D.O.; Murungi, Maurice K.; Wambua, Lillian; Bastos, A.D.S.; Fèvre, Eric M.; Falzon, Laura C. (Springer, 2021)
Background Tick-borne pathogens (TBPs) are of global importance, especially in sub-Saharan Africa where they represent a major constraint to livestock production. Their association with human disease is also increasingly recognized, signalling their zoonotic importance. It is therefore crucial to investigate TBPs prevalence in livestock populations and the factors associated with their presence. We set out to identify TBPs present in cattle and to determine associated risk factors in western Kenya, where smallholder livestock production is important for subsistence and market-driven income. Results Tick-borne pathogen infections in blood samples collected from cattle at livestock markets and slaughterhouses between May 2017 and January 2019 were identified by high-resolution melting analysis and sequencing of PCR products of genus-specific primers. Of the 422 cattle sampled, 30.1% (127/422) were infected with at least one TBP, while 8.8% (37/422) had dual infections. Anaplasma spp. (19.7%) were the most prevalent, followed by Theileria (12.3%), Ehrlichia (6.6%), and Babesia (0.2%) spp. Sequence analysis of the TBPs revealed them to be Anaplasma platys-like organisms (13.5%), Theileria velifera (7.4%), Anaplasma marginale (4.9%), Theileria mutans (3.1%), Theileria parva (1.6%), and Babesia bigemina (0.2%). Ehrlichia ruminantium, Rickettsia spp., and arboviruses were not detected. Exotic breeds of cattle were more likely to be infected with A. marginale compared to local breeds (OR: 7.99, 95% CI: 3.04–22.02, p < 0.001). Presence of ticks was a significant predictor for Anaplasma spp. (OR: 2.18, 95% CI: 1.32–3.69, p = 0.003) and Ehrlichia spp. (OR: 2.79, 95% CI: 1.22–7.23, p = 0.022) infection. Cattle sampled at slaughterhouses were more likely to be positive for Anaplasma spp. (OR: 1.64, 95% CI: 1.01–2.70, p = 0.048) and A. marginale (OR: 3.84, 95% CI: 1.43–12.21, p = 0.012), compared to those sampled at livestock markets. Conclusion This study reports TBP prevalence and associated risk factors in western Kenya, factors which are key to informing surveillance and control measures.